Malignant epithelia cells-derived spermine induces APOE+ macrophages to suppress tumor immunity in adenocarcinoma of the esophagogastric junction - Zhang, Yan; Liu, Zhaoyang; Sun, Huihui; Wang, Zhenxiang; Chen, Ye; Hu, Zhiqian; Li, Xinxing; Xu, Kai; Chen, Ying; Xu, Yanping; Wang, Chenfei; Xu, Shuchang (Frontiers in Medicine, 2025)
BackgroundAdenocarcinoma of the esophagogastric junction (AEG) is increasingly recognized as a distinct gastrointestinal tumor type with a poor prognosis. However, the mechanisms driving AEG progression, particularly the interplay between metabolic reprogramming and the immune microenvironment, remain poorly understood.MethodsWe integrated multi-omics to profile the tumor microenvironment and metabolic reprogramming of AEG. Tumor tissues and paired normal adjacent tissues from AEG patients were subjected to single-cell RNA sequencing (N=11), spatial transcriptomics (N=4), and metabolomics analysis (N=26). Molecular experiments and animal models were used for validation.ResultsOur analysis revealed an AEG-specific malignant subtype originating from the esophagogastric junction, characterized by heightened proliferation and poor differentiation. These malignant cells exhibited metabolic reprogramming marked by hyperactivation of the glutamine-arginine-spermine axis with concomitant spermine accumulation. Spermine was found to drive the polarization of tumor-associated macrophages into an APOE+ immunosuppressive phenotype, thereby modulating the tumor immune microenvironment. Mechanistically, spermine promoted the phosphorylation of STAT3, thereby enhancing its binding affinity to the APOE promoter region and leading to enhanced transcriptional activation of APOE.ConclusionThis study identified AEG-like malignant cells as a high-risk subtype, revealed the metabolic-immune crosstalk driven by the spermine-STAT3-APOE axis in AEG progression, and provided potential targets for AEG metabolic intervention and immunotherapy.